2001
DOI: 10.1039/b101449h
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of solvent–solute interactions in room temperature ionic liquids using solvatochromic dyes

Abstract: Different measures of polarity and nucleophilicity of a range of ionic liquids have been investigated using two solvatochromic dyes; the polarity appears to be largely cation controlled, while the donor strength is entirely anion dependent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

34
376
1
6

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 395 publications
(417 citation statements)
references
References 17 publications
34
376
1
6
Order By: Relevance
“…The values of solvent polarity ET(30) 19) for organic nitrogen compounds are about 40 kcal/mol and about 34 kcal/mol for aromatic compounds, suggesting that organic nitrogen compounds are more polar than aromatic compounds. The values of ET(30) for ionic liquids 20) are larger than 50 kcal/mol, suggesting that ionic liquids interact well with more polar compounds. Therefore, the present study found that permeation rates through the SLM based on ionic liquids were mainly controlled by the polarity of the permeating species; but species hydrophilicity should be considered if the polarities are similar.…”
Section: Resultsmentioning
confidence: 99%
“…The values of solvent polarity ET(30) 19) for organic nitrogen compounds are about 40 kcal/mol and about 34 kcal/mol for aromatic compounds, suggesting that organic nitrogen compounds are more polar than aromatic compounds. The values of ET(30) for ionic liquids 20) are larger than 50 kcal/mol, suggesting that ionic liquids interact well with more polar compounds. Therefore, the present study found that permeation rates through the SLM based on ionic liquids were mainly controlled by the polarity of the permeating species; but species hydrophilicity should be considered if the polarities are similar.…”
Section: Resultsmentioning
confidence: 99%
“…Although hydrophobic ILs have relatively high polarity, 22 many kinds of metal cations are extracted as neutral complexes in IL chelate extraction as well.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, it has been reported that E T (30) for Bmim-TFSA is 50-52 kcal/mol. 50 When we used 52 kcal/mol as E T (30), ν Stokes of BPH was calculated to be 2084 cm -1 , which represents a 384 cm -1 difference from the measured value. Because the fluorescence lifetime in Bmim-TFSA was the same as that in acetonitrile, the interaction of BPH(D 1 ) with Bmim-TFSA may have been similar to that with acetonitrile, as previously suggested by non-equilibrium molecular dynamics simulations.…”
Section: Resultsmentioning
confidence: 99%